Preparation of hydrogel based on cellulose from sugarcane bagasse - Ha, Nguyen Thu; Quyen, Nguyen Thi; Duc, Vu Anh; Hang, Hoang Thu; Ha, Do Thu; Anh, Tran Ngoc; Mai, Nguyen Ngoc (Vietnam Journal of Science and Technology, 2026)
In this study, the preparation and characterization of hydrogels from sugarcane bagasse were investigated. The preparation of hydrogels was made with cellulose extracted from sugarcane bagasse, ammonium persulfate as an initiator, acrylic acid as a monomer, and N,N’-methylenebisacrylamide as a crosslinking agent. The characterization of structure and properties of the hydrogels were carried out through Fourier-transform Infrared spectroscopy, Focused Ion Beam Scanning Electron Microscopy, and the determination of Young’s modulus, tensile strength, elongation at break and Charpy impact, swelling degree and Thermogravimetric Analysis. The suitable conditions for the preparation were found to be 1.0 g ammonium persulfate/kg cellulose, 1.6 g acrylic acid/kg cellulose and 0.2 g N,N’-methylenebisacrylamide/kg cellulose. It was found that both anions and cations can be absorbed into the crosslinked structure of the hydrogel. The Young’s modulus, tensile strength, elongation at break, and Charpy impact of the hydrogel prepared under the suitable conditions were 1.3 MPa, 5.2 MPa, 89.0 % and 7.2 kJ/m2, respectively. The hydrogel has better thermal resistance than the cellulose. The results show that the hydrogel obtained may be suitable for use as an electrolyte membrane in batteries.